Circ_0002623 promotes bladder cancer progression by regulating the miR‐1276/SMAD2 axis. Issue 4 (3rd March 2022) - Zhang, Zhaocun; Zhao, Haifeng; Zhou, Guanwen; Han, Ruoyan; Sun, Zhuang; Zhong, Minglei; Jiang, Xianzhou
Abstract: Circular RNAs (circRNAs) are key regulatory factors in the development of multiple cancers. This study is targeted at exploring the effect of circ_0002623 on bladder cancer (BCa) progression and its mechanism. Circ_0002623 was screened out by analyzing the expression profile of circRNAs in BCa tissues. Circ_0002623, miR‐1276, and SMAD2 mRNA expression levels in clinical sample tissues and cell lines were detected through quantitative real‐time polymerase chain reaction (qRT‐PCR). After circ_0002623 had been overexpressed or silenced in BCa cells, the cell proliferation, migration, and cell cycle were evaluated by CCK‐8, BrdU, Transwell assay, and flow cytometry. Tumor xenograft model was used to validate the biological function of circ_0002623 in vivo. Bioinformatics analysis and dual‐luciferase reporter gene assay were conducted for analyzing and confirming, respectively, the targeted relationship between circ_0002623 and miR‐1276, as well as between miR‐1276 and SMAD2. The regulatory effects of circ_0002623 and miR‐1276 on the expression levels of TGF‐β, WNT1, and SMAD2 in BCa cells were detected by Western blot. We reported that, in BCa tissues and cell lines, circ_0002623 was upregulated, whereas miR‐1276 was downregulated. Circ_0002623 positively regulated BCa cell proliferation, migration, and cell cycle progression. Additionally, circ_0002623 could competitively bind with miR‐1276 to increase the expression of SMAD2, the target gene of miR‐1276. Furthermore, circ_0002623 could regulate the expression of TGF‐β and WNT1 via modulating miR‐1276 and SMAD2. This study helps to better understand the molecular mechanism underlying BCa progression. Abstract : Mechanism research indicated that circ_0002623 increased SMAD2 expression via sponging miR‐1276, thereby promoting the malignant phenotype of bladder cancer (BCa) cells.